2021
DOI: 10.1007/s12061-021-09381-8
|View full text |Cite|
|
Sign up to set email alerts
|

Progress Towards Using Linked Population-Based Data For Geohealth Research: Comparisons Of Aotearoa New Zealand And The United Kingdom

Abstract: Globally, geospatial concepts are becoming increasingly important in epidemiological and public health research. Individual level linked population-based data afford researchers with opportunities to undertake complex analyses unrivalled by other sources. However, there are significant challenges associated with using such data for impactful geohealth research. Issues range from extracting, linking and anonymising data, to the translation of findings into policy whilst working to often conflicting agendas of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…15 Moreover, the rapid digitalisation of health, education and broader social systems and significant improvements in data processing and storage capabilities have allowed researchers to access several sources of novel data not previously available, such as linked nationwide data on households, education, and employment. 16 Efforts continue to be made to model infectious disease transmission using complex systems approaches. 14 With advances in computing power, the utility of networks to analyse numerous sources of data have increased dramatically, 17,18 and studies employing network analysis to understand disease transmission patterns are increasingly popular.…”
Section: Implication Of All the Available Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…15 Moreover, the rapid digitalisation of health, education and broader social systems and significant improvements in data processing and storage capabilities have allowed researchers to access several sources of novel data not previously available, such as linked nationwide data on households, education, and employment. 16 Efforts continue to be made to model infectious disease transmission using complex systems approaches. 14 With advances in computing power, the utility of networks to analyse numerous sources of data have increased dramatically, 17,18 and studies employing network analysis to understand disease transmission patterns are increasingly popular.…”
Section: Implication Of All the Available Evidencementioning
confidence: 99%
“… 15 Moreover, the rapid digitalisation of health, education and broader social systems and significant improvements in data processing and storage capabilities have allowed researchers to access several sources of novel data not previously available, such as linked nationwide data on households, education, and employment. 16 …”
Section: Introductionmentioning
confidence: 99%
“…The use of record linkages across different types of datasets is becoming increasingly important in advancing the measurement and understanding of socio-spatial inequalities in health, especially among minority or hard-to-sample populations [ 1 , 2 , 3 , 4 ]. In several high-income countries, studies using representative surveys or administrative data alone (unlinked) have demonstrated disparities in mental health, psychiatric morbidity, and problematic substance use among sexual minorities, including lesbian, gay, and bisexual (LGB) adults [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%